Design of a Siam Orange Ripeness Detection Application using the HSI (Hue, Saturation, Intensity) Method - Sembiring, Ade Rofanggi; Hendrik, Jackri; Pribadi, Octara (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Siam orange (Citrus tangerina), commonly known in English as tangerine, is an orange-colored citrus fruit that is very closely related to, or possibly a type of, mandarin orange (Citrus reticulata). The name was originally used for fruits from Tangier, Morocco, which were described as a variety of mandarin. Under the Tanaka classification system, Citrus tangerina is considered a separate species. In contrast, under the Swingle system, Siam orange is regarded as a group within the mandarin (C. reticulata) varieties